Onion Growers’ Adaptation Strategies in the Context of Thailand–China Free Trade Agreement: The Case Study of Chiang Mai Province, Thailand - Thinnarach, Nawan; Ngamsomsuke, Kamol; Ekasingh, Benchaphun; Wongchai, Anupong (Journal of Applied Economics and Management Strategy, 2023)
The study aimed to investigate adaptation strategies of the onion growers in response to the impact of Thailand-China Free Trade Agreement and their fostering factors in Chiang Mai province of Thailand. Multinomial logit regression was used to analyze factors fostering the three strategies namely production and marketing adjustment, request to postpone import or no adaptation. These strategies were grouped from the six strategies adopted among onion growers in the area. The analysis showed that only three factors, and their interaction were among the tested factors included in the best fitted model. The investment in the production (production cost) and access to Thailand–China FTAs information of the household head as well as interaction between production cost and household income were statistically determinant of the adaptation strategies. In more detail, onion growers with higher investment in the production or household head had access to Thailand–China FTAs information would choose to strategy on adjusting the production or marketing activities. Onion growers with higher investment in the production and producing household income would choose strategy on the request to postpone import of onion into the country from February to August or no adaptation.